The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1515/chem-2015-0146
|View full text |Cite
|
Sign up to set email alerts
|

Production of calcium preparations by technology of saltwater fish by product processing

Abstract: Abstract:The paper presents the technology of processing Baltic cod (Gadus morhua callarias) and Atlantic salmon (Salmo salar) backbones -by-products from fish processing -for the production of calcium preparations. The raw material for the process consisted of backbones with remaining muscle tissue, devoid of heads and fins (30 kg of each type of backbones). The processing included the following stages: cutting, preliminary processing in an alkaline environment (soaking in 2 M NaOH), processing with 0.1% citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Using microbial enzymes can be seen as a feasible approach from an economic point of view [54]. In the case of minerals, the preparation of mineral-rich products could be obtained by simple and low-cost operations such as treating the fish bones with weak solutions (alkali, acid, and hydrogen peroxide), followed by drying and grinding [55].…”
Section: Mineralsmentioning
confidence: 99%
“…Using microbial enzymes can be seen as a feasible approach from an economic point of view [54]. In the case of minerals, the preparation of mineral-rich products could be obtained by simple and low-cost operations such as treating the fish bones with weak solutions (alkali, acid, and hydrogen peroxide), followed by drying and grinding [55].…”
Section: Mineralsmentioning
confidence: 99%
“…The alkaline treatment is more common method to extract the fish bone powder from fish filleting frame (Kettawan et al, 2002). Bubel et al, (2015) studied essential mineral content of fish bone powder from Baltic cod (Gadus morhua callarias) and Atlantic salmon (Salmo salar) filleting frame using extraction methods like an alkaline environment (soaking in 2 M NaOH, Sodium Hydroxide), processing with 0.1% citric acid (aroma removal) and 5% H 2 O 2 (Hydrogen Peroxide) as disinfection, rinsing with tap water, drying, and grinding the endproduct. The recovery of components with potential biological activities and functionalities provides a means for value addition to the fish processing waste and also add to plant economy.…”
mentioning
confidence: 99%
“…A previous study showed that alkaline treatment of backbones (Baltic cod and tic salmon) after removal of muscle tissue resulted in a bone powder with a con 27.79% and 24.92% calcium, 13.40% and 12.50% phosphorus, 0.66% and 0.46% magn and 0.030% and 0.027% potassium in the preparations from Baltic cod and A salmon, respectively. Protein contents were 15% and 18% in the powders obtained Baltic cod and Atlantic salmon, respectively [17]. Hence, the alkaline treatment o bone rinsed from muscle tissue resulted in higher contents of calcium and phosp whereas the contents of the minerals magnesium and potassium and proteins were Moreover, calcination (700 °C, 2 h) treatment of fish bones from different species (c tilapia, seabass and tuna) also resulted in higher contents of calcium and phosphor lower contents of magnesium and potassium [18].…”
Section: Content Of Minerals In the Bone Powder Products And Raw Cod ...mentioning
confidence: 95%